The Faber book of modern verse - Roberts, Michael, 1902-1948 (Faber and Faber, 1982)
The Faber Book of Modern Verse was a poetry anthology, edited in its first edition by Michael Roberts, and published in 1936 by Faber and Faber. There was a second edition (1951) edited by Anne Ridler, and a third edition (1965) edited by Donald Hall. The selection was of poems in English printed after 1910, which meant that work by Gerard Manley Hopkins could be included. A later edition was edited by Peter Porter.